Oil painting within the framework of art education to support local ethnic cultures and preserve cultural heritage in China - Wang, Beibei (Arte, Individuo y Sociedad, 2023)
The purpose is to compare the development of innovative thinking in two groups of students who learn the intangible cultural heritage of the ancient ethnic group and master oil painting techniques in two formats: distantly and visiting the Miao settlement in the deep southeast of Guizhou. In addition to the traditional learning of oil painting techniques, the students learnt folklore and the cultural heritage of ethnic minorities as a part of the art curriculum. For practice, the control group (96 students) visited the villages of Miao in Guizhou, and the experimental group (96 students) gained experience and knowledge about the Miao ethnic minority distantly, through videos and e-discussions. At the end of the training, the students presented their final oil paintings on the life of the Miao. They have been assessed by teachers and art critics to identify innovative thinking among students as a driving force of creativity. The control group showed higher results on parameters such as Integrity (454 points) and Flexibility (287 points). The high-end result of the control group proved that innovative thinking is best developed by immersing students in the real world of the Miao and allowing them to experiment and feel their works.